IL-1α and IL-36 Family Cytokines Can Undergo Processing and Activation by Diverse Allergen-Associated Proteases - Frezza, Valentina; Najda, Zaneta; Davidovich, Pavel; Sullivan, Graeme P.; Martin, Seamus J. (Frontiers in Immunology, 2022)
Inflammation driven by environmental allergens is an important source of morbidity in diseases such as asthma and eczema. How common allergens promote inflammation is still poorly understood, but previous studies have implicated the protease activity associated with many allergens as an important component of the pro-inflammatory properties of these agents. The IL-1 family cytokine, IL-33, has recently been shown to undergo processing and activation by proteases associated with multiple common allergens. However, it remains unclear whether the sensing of exogenous protease activity—as a proxy for the detection of invasive microbes, allergens and parasitic worms—is a general property of IL-1 family cytokines. In common with the majority of IL-1 family members, cytokines within the IL-36 sub-family (IL-36α, IL-36β and IL-36γ) are expressed as inactive precursors that require proteolysis within their N-termini for activation. Here we show that proteases associated with multiple common allergens of plant, insect, fungal and bacterial origin (including: Aspergillus fumigatus, ragweed, rye, house dust mite, cockroach and Bacillus licheniformis) are capable of processing and activating IL-36 family cytokines, with IL-36β being particularly susceptible to activation by multiple allergens. Furthermore, extracts from several allergens also processed and enhanced IL-1α activity. This suggests that multiple IL-1 family cytokines may serve as sentinels for exogenous proteases, coupling detection of such activity to unleashing the pro-inflammatory activity of these cytokines. Taken together with previous data on the diversity of proteases capable of activating IL-1 family cytokines, this suggests that members of this cytokine family may function as ‘activity recognition receptors’ for aberrant protease activity associated with infection, tissue injury or programmed necrosis.